Determination of antioxidation activities of Sarawak’s traditional herb kacangma leonurus sibiricus - Chua, Hun Pin; Aminah Abdullah (Universiti Kebangsaan Malaysia, 2010)
Antioxidant activities of ethanolic and aqueous extract from kacangma (Leonurus sibiricus) were determined by using three model systems. Based on the antioxidant activity range, ethanolic extract of dried kacangma was high in oxidation of linoleic acid lipid system (LP) 71.6%, moderate in xanthine oxidase superoxide scavenging activity (XOD) 69.7% and low in 1,2-diphenyl-2-picrylhydrazyl radical scavenging activity (DPPH) 48.8%. On the other hand, aqueous extract of dried kacangma was high in antioxidant activities for all three bioassays with mean percentages of 72.7, 76.3 and 78.2%, respectively. Extraction in water was more efficient than ethanol in extracting the antioxidants present in dried kacangma.